It outsourcing and redefinition of the subsidiary role: a comparative study between the brazilian and the indian subsidiaries of an american multinational (Journal of Information Systems and Technology Management, 2009)
Global outsourcing, also known as offshoring, has become a major phenomenon in the IT industry. Responsibilities have been transferred to IT suppliers worldwide. A key element of this strategic change occurred in the IT sector is the growing importance of emerging economies, such as Brazil and India, as offshoring suppliers. A stream of the literature on international business has analysed which factors may affect the evolution of a subsidiary within a multinational. This paper aims to analyse how exporting outsourcing IT services can redefine the role of a subsidiary within a corporation and, consequently change its strategic relevance. Empirical research compared the offshoring activities of two subsidiaries -Brazilian and Indian - of an American IT multinational. In particular, the empirical research focussed on how subsidiary choice, head office assignment and environment determinism factors interact to each other in order to determine the evolution of each subsidiary. The results have demonstrated that the Indian subsidiary trajectory was essentially determined by the development of its resources, innovation, governmental support and entrepreneurship. The Brazilian subsidiary trajectory in turn was mostly influenced by head office assignment and subsidiary performance. A comparative analysis between the two cases has demonstrated how these aspects have altogether determined why these subsidiaries have evolved differently from each other. Most importantly, this paper argues that management capacity and subsidiary leadership are critical elements to understand the evolution of a multinational subsidiary trajectory.